Limited Liability Company, LLC Legal Model and Its Evolution: An Analysis of Georgia and European Practice - Topchishvili, Eter (European Scientific Journal, ESJ, 2026)
This article examines the legal nature, regulatory development, and contemporary significance of the limited liability company (LLC) within Georgian corporate law. The primary objective of the study is to determine how the concept of limited liability has been incorporated and transformed within the Georgian legal system and to assess whether the current regulatory framework adequately reflects both doctrinal foundations and European legal standards. The research is based on a doctrinal legal analysis of legislative acts governing entrepreneurial activity in Georgia, including the 1991 Law on the Fundamentals of Entrepreneurial Activity, the 1994 Law on Entrepreneurs, and the comprehensive reform of 2021 adopted in the context of obligations arising from the Association Agreement with the European Union. In addition, the article employs a comparative legal review to evaluate the approximation of Georgian LLC regulation to European corporate law principles. The study analyzes the theoretical foundations of legal personality, the defining characteristics of an LLC, registration procedures, and the role of registration authorities. Particular attention is paid to the principle of limited liability as a mechanism for risk allocation and protection of personal assets. The findings demonstrate that the LLC has evolved into the dominant and most flexible business form in Georgia due to its capacity to balance entrepreneurial freedom with creditor protection. Furthermore, the 2021 reform significantly strengthened legal certainty and enhanced alignment with European standards, thereby reinforcing the LLC’s role as a key instrument for economic development and investment attraction.